PENGARUH ASET PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN JASA SUB SEKTOR KONSTRUKSI DAN BANGUNAN YANG TERDAFTAR DI BEI - Melani Agustina; Paul Eduard Sudjiman (Fakultas Ekonomi Universitas Advent Indonesia, 2022)
This study will discuss the effect of deferred tax assets on earnings management in construction and building sub-sector service companies listed on the IDX. This study uses quantitative analysis with primary and secondary data collection, in addition to the analysis of data processing researchers use SPSS 22 as a supporting part. There are 18 construction and building sub-sector service companies listed on the IDX in 2016-2020, with 7 samples of companies that match the criteria that the researcher has provided. The results of the T-test analysis show that changes in the number of Deferred Tax Assets have an influence on Earnings Management in the construction and building sub-sector service companies. Where if the number of Deferred Tax Assets changes, it will cause the Earnings Management number to change as the Deferred Tax Assets number changes. With the results obtained in the form of a significant influence of deferred tax assets on earnings management in the companies studied.